Respuesta :
Answer:
c > 1
Step-by-step explanation:
Given equation: [tex]x^2-2x+c=0[/tex]
General form of quadratic equation: [tex]ax^2+bx+c=0[/tex]
We can use the discriminant to determine the value of c for which the equation has no real roots.
[tex]b^2-4ac < 0\implies \textsf{no real roots}[/tex]
From the given equation:
- [tex]a=1[/tex]
- [tex]b=-2[/tex]
- [tex]c=c[/tex]
Inputting these values into the discriminant formula:
[tex]\implies (-2)^2-4(1)(c) < 0[/tex]
[tex]\implies 4-4c < 0[/tex]
[tex]\implies 4 < 4c[/tex]
[tex]\implies 1 < c[/tex]
[tex]\implies c > 1[/tex]
Here
- a=1
- b=-2
Discriminant must be less than 0
[tex]\\ \rm\Rrightarrow b^2-4ac<0[/tex]
[tex]\\ \rm\Rrightarrow (-2)^2-4(1)(c<0[/tex]
[tex]\\ \rm\Rrightarrow 4-4c<0[/tex]
[tex]\\ \rm\Rrightarrow 4(1-c)<0[/tex]
[tex]\\ \rm\Rrightarrow 1-c<0[/tex]
[tex]\\ \rm\Rrightarrow 1<c[/tex]
[tex]\\ \rm\Rrightarrow c>1[/tex]